Characterization and mechanism of crystallization of Ge films on silicon substrate with graphite buffer layer. (September 2018) - Tao, Quanli; Chen, NuoFu; Wang, Congjie; Dayan, Ma; Bai, Yiming; Chen, Jikun
Abstract: The highly crystallized Ge films have been fabricated by magnetron sputtering and thermal annealing on silicon substrate with a graphite buffer layer which can reduce the lattice mismatch and thermal mismatch. In this paper, we demonstrate the effects of substrate temperature and annealing parameters on Ge film quality through XRD and Raman measurements. The mechanism of the Ge films crystallization during the annealing process is analyzed using the lowest energy principle and the law of Bravais.